Surgical Management of a Giant Desmoid Fibromatosis of Abdominal Wall With Vessels Invasion in a Young Man: A Case Report and Review of the Literature - Zhao, Jiming; Cheng, Fajuan; Yao, Zhigang; Zheng, Bin; Niu, Zhihong; He, Wei (Frontiers in Surgery, 2022)
Background: Desmoid fibromatosis (DF) is a rare clonal proliferation of fibroblasts and myofibroblasts. It develops in the connective tissues and do not metastasize but may infiltrate adjacent structures. Because of the rarity of these tumors and unpredictable natural history of disease, well-defined and precise guidelines of the optimal treatment for desmoid fibromatosis have not been formulated. Case presentation: Here, we present a case of a giant abdominal desmoid fibromatosis that invaded the right spermatic cord and iliac vessels. The lesion was excised with external iliac artery dissection; however, the vein was sacrificed. The abdominal wall defect was then repaired with a polypropylene mesh. The lesional cells are positive for β-Catenin. Conclusions: In the past decades, there has been a change in the treatment of desmoid fibromatosis. The “wait and see” policy has been considered initially in most cases. Surgical intervention remains a valid option for symptomatic lesions. The optimal regimes of the tumor should not take the risk of making the patient more symptomatic than the lesion itself.